(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the problems of the relationship between assessment and norms, the subjectivity of the choice of norms, reveals the role of the context and the situation of communication in the evaluation process, the influence of the characteristics of the worldview of the speaker’s personality, his value orientations and speech behavior.